Spesies Gastropoda Pada Saluran Irigasi Di Desa Air Satan - Tria Octaviany; Riya Amelia; Zhafirah Aulia; Jimi Brandia; Dian Samitra (Prosiding Silampari Conference of Life Sciences and Techonology (Silamparilist), 2026)
Gastropods are a class within the phylum Mollusca that play a crucial role in aquatic ecosystems, both as detritivores and as bioindicators of environmental quality. This study aims to determine the species diversity of gastropods in irrigation channels in Air Satan Village. Irrigation channels, as artificial aquatic ecosystems, provide habitats for various aquatic organisms, including gastropods, whose presence is influenced by environmental conditions such as water flow, substrate, temperature, and the availability of organic matter. This study employed a field survey method using the hand-collecting sampling technique at several observation points along the irrigation channels. Sampling was conducted directly by manually collecting gastropods found on the substrate surface, rocks, aquatic vegetation, or the water bottom. Species identification was based on morphological characteristics using relevant taxonomic literature. The data obtained were analyzed descriptively. The study identified the following gastropod species: Achatina fulicata, Filopaludina javanica, Melanoides tuberculata, Pilus ampullacea, Pomacea canaliculata, Subulina octona, Oxcychilus draparnaudi, and Laevicaulis alte. It was concluded that eight gastropod species were found in the irrigation channels of Air Satan Village. This study is expected to provide an overview of the gastropod community structure and the ecological conditions of the irrigation channels in Air Satan Village. This information is important.